2005
DOI: 10.1177/1049731505276321
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Training Programs in Child Welfare Services: Planning for a More Evidence-Based Approach to Serving Biological Parents

Abstract: Child welfare service agencies provide parent training as part of their legally mandated responsibility to provide services to assist families to keep their children at home or to achieve reunification. The use of parent-training programs for families in the child welfare system has undergone relatively little examination. Mental health, special education, and juvenile justice have been identifying evidence-based approaches that have demonstrated effectiveness with children and families with conduct disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
165
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(169 citation statements)
references
References 60 publications
1
165
0
3
Order By: Relevance
“…Os programas de educação parental estão a ser largamente usados noutros países (como por exemplo, Canadá, Estados Unidos da América, País de Gales e Inglaterra) pelos serviços de apoio à infância, com o objetivo de prevenir situações de mal trato infantil, promovendo competências parentais em famílias com fatores de risco (Barth et al, 2005;Sanders, Cann, & Markie-Dadds, 2003), numa lógica de prevenção secundária e com resultados bastante promissores.…”
Section: Educação Parental Em Famílias Maltratantes -Uma Luz Ao Fundounclassified
See 1 more Smart Citation
“…Os programas de educação parental estão a ser largamente usados noutros países (como por exemplo, Canadá, Estados Unidos da América, País de Gales e Inglaterra) pelos serviços de apoio à infância, com o objetivo de prevenir situações de mal trato infantil, promovendo competências parentais em famílias com fatores de risco (Barth et al, 2005;Sanders, Cann, & Markie-Dadds, 2003), numa lógica de prevenção secundária e com resultados bastante promissores.…”
Section: Educação Parental Em Famílias Maltratantes -Uma Luz Ao Fundounclassified
“…Os estudos demonstram, de uma forma bastante consensual, a ideia que a educação parental, ao disponibilizar aos pais formas alternativas, eficazes e positivas, para lidar com o comportamento dos seus filhos, pode ser útil para a prevenção e redução dos problemas de comportamento destes (Webster-Stratton, 2007;Webster-Stratton & Reid, 2006); diminuição dos comportamentos antisociais e criminais (Hutchings et al, 2006) e prevenção do consumo de substâncias psicoativas (Kumpfer & Johnson, 2007); e prevenção dos maus tratos (Barth, 2009;Barth & Haskins, 2009;Barth et al, 2005;Britner & Reppucci, 1997;Jouriles et al, 2010;Letarte, Normandeau, & Allard, 2010;Whipple & Wilson, 1996).…”
Section: Educação Parental Em Famílias Maltratantes -Uma Luz Ao Fundounclassified
“…Services to the hundreds of thousands of children who remain in their homes come in the form of parent-focused services. Although there are numerous, efficacious parent-focused interventions that can change the family environment and improve the lives of children, research has documented that most of the parent focused interventions currently delivered to families in child welfare and most foster family training do not use treatment strategies with solid empirical support (Hurlburt et al 2007; Barth et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Parents who fail to demonstrate adequate parenting skills may lose their parental rights, although there is little evidence to indicate that parents involved in the child welfare system have inadequate parenting skills. For instance, Barth et al (2005) found that only 33% of the caregivers who lost their custodial rights were identified by child welfare professionals as having poor parenting skills. In sum, parental competence needs to be determined by whether parents with substance use disorders can provide a safe and stable home environment for their children (Steinhauer, 1991).…”
Section: Mental Healthmentioning
confidence: 99%